2000
DOI: 10.1590/s0004-282x2000000300020
|View full text |Cite
|
Sign up to set email alerts
|

Distonia psicogênica: relato de dois casos

Abstract: RESUMO -Desordens de movimento raramente podem ser devidas a distúrbios psiquiátricos. A distonia psicogênica caracteriza-se pela inconsistência dos achados, presença de fatores precipitantes, manifestar-se inicialmente nos membros inferiores, associar-se a dor, a outros movimentos anormais incaracterísticos e a somatizações múltiplas. Descrevemos duas pacientes com diagnóstico de distonia psicogênica clinicamente estabelecida. Paciente 1, feminina, apresentou episódio súbito de perda de força dos quatro membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…104 Laboratory tests can be used to exclude other possible causes for dementia 89 such as cerebrovascular disease, cobalamin deficiency, syphilis, or thyroid disease. [105][106][107] Cerebrospinal fluid (CSF) analysis can be useful in identifying dementia caused by other factors, including infections in the central nervous system (CNS) such as neurosyphilis, neuroborreliosis, and cryptococcosis. 108 The CSF levels of tau and phosphorylated tau are often elevated in AD, whereas amyloid levels are usually low.…”
mentioning
confidence: 99%
“…104 Laboratory tests can be used to exclude other possible causes for dementia 89 such as cerebrovascular disease, cobalamin deficiency, syphilis, or thyroid disease. [105][106][107] Cerebrospinal fluid (CSF) analysis can be useful in identifying dementia caused by other factors, including infections in the central nervous system (CNS) such as neurosyphilis, neuroborreliosis, and cryptococcosis. 108 The CSF levels of tau and phosphorylated tau are often elevated in AD, whereas amyloid levels are usually low.…”
mentioning
confidence: 99%
“…Antonio Pedro Vargas and colleagues 8 have shown the clinical characteristics of two patients with psychogenic gait abnormalities and the difficult differential diagnosis; Roberta de Melo Roiz and colleagues 9 have shown, using kinematics data, that in 12 patients with Parkinson's disease (compared to 15 controls) there was a lower stride velocity, shorter stride length and slower hip joint kinematics; and Eliane Mayumi Kato-Narita and colleagues 10 have shown that in 48 patients with mild and moderate Alzheimer's disease (AD) (compared to 40 normal subjects) there was a decline of balance asso-ciated to the occurrence of falls, but interestingly the loss of functional capacity was associated with the disease's progression but not with a higher occurrence of falls. Péricles Maranhão-Filho and colleagues 4,5 are to be commended for bringing back the fundamental issue of the neurologic examination and for explaining in details how to perform and correctly interpret a modern and elegant evaluation of stance and gait.…”
mentioning
confidence: 99%